Bronchoscopy pada Pasien Atelektasis dengan Traumatic Brain Injury di ICU - Niko Pamillian Ariesti; Calcarina Fitriani Retno Wisudarti (Lembaga Pengembangan Kinerja Dosen, 2026)
Pathological brain-lung crosstalk severely complicates the intensive management of traumatic brain injury (TBI). Pulmonary complications such as atelectasis and ventilator-associated pneumonia (VAP) frequently worsen patient outcomes by prolonging mechanical ventilation and increasing morbidity. This report analyzes the clinical dynamics of a patient with severe TBI who developed refractory atelectasis and early-onset VAP during intensive care management. A male patient presenting after blunt trauma with massive, multifocal intracranial hemorrhages required urgent decompressive craniectomy and invasive mechanical ventilation. During intensive care, the patient developed persistent right upper lobe atelectasis, which subsequently precipitated VAP caused by an extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli. Performing flexible bronchoscopy in neurocritical patients carries a significant risk of intracranial pressure (ICP) elevation secondary to auto-positive end-expiratory pressure (auto-PEEP) generation and transient hypercapnia. Therefore, strict periprocedural mitigation strategies, including complete pharmacological paralysis, optimization of pressure-regulated volume control ventilation, intermittent bronchoscope insertion, and continuous hemodynamic and neurological monitoring, were implemented throughout the procedure. Therapeutic bronchoscopy remains an effective and safe intervention for resolving post-TBI atelectasis when carefully integrated with neuroprotective ventilation strategies designed to minimize intracranial pressure elevation and optimize respiratory function, thereby supporting favorable clinical outcomes in neurocritical care patients.